Brain Bioelectric Responses to Short-Term Heart Rate Variability Biofeedback Training in Indian and Russian University Students Studying in the Russian Arctic - Denis Demin; Liliya Poskotinova (Life)
Heart rate variability biofeedback (HRV BF) training aids adaptation to new climatic, geographical, and social environments. Neurophysiological changes during the HRV BF in individuals from tropical regions studying in the Arctic are not well understood. The aim of this study was to research electroencephalographic (EEG) changes during a single short-term HRV BF session in Indian and Russian students studying in the Russian Arctic. The Indian (n = 40) and Russian (n = 40) healthy students (age 19–21 years) at a medical university in Arkhangelsk (64°33′ N 40°32′ E) were studied. HRV and EEG parameters were measured at baseline (5 min) and during a short-term HRV BF session (5 min) to increase the total power (TP, ms2) of the HRV spectrum. The baseline heart rate and stress index levels were significantly higher in the Indian students. During the HRV BF sessions, the sympathetic activity decreased more significantly in Russian students, while the alpha EEG activity significantly increased across all brain regions in both groups. In Indian students, there was a notable increase in theta and beta1 EEG spectral power in the frontal, central, and temporal regions. HRV BF training in Indian students was associated with a more pronounced activation of brain systems compared with Russian students.